Passing the Buck : Congress, the Budget, and Deficits. - Farrier, Jasmine (The University Press of Kentucky, 2015)
In the past thirty years, Congress has dramatically changed its response to unpopular deficit spending. While the landmark Congressional Budget Act of 1974 tried to increase congressional budgeting powers, new budget processes created in the 1980s and 1990s were all explicitly designed to weaken member, majority, and institutional budgeting prerogatives. These later reforms shared the premise that Congress cannot naturally forge balanced budgets without new automatic mechanisms and enhanced presidential oversight. So Democratic majorities in Congress gave new budgeting powers to Presidents Rea.